Paradigma Keagamaan dan Politik Organisasi KAMMI Daerah Jambi - Ulum, Bahrul (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
The purpose of this researclt is to investigate the political paradigm and religiousity of the KAMMI (the Front Action of the Indonesian Muslim Students) in Jambi. In this study, the qualitative approach was applied in which the writer himself actively participated as the research instrument. The writer finds that the KAMMI ideology of Islam has influenced their tradition in understanding Islam. This happens as the consequence of their training namely the tarbiyah in which the Islamic teaching of their own is only taken for granted by the members. The narrow and strict understanding of the members finally reflects in their daily activities in Islamic symbolism. Their view that Islam doesnt allow the separation between the substantial and the formal finally influence their vision that the Islamic state is more important to implement the syariah, and this what the writer sees the similar vision with the neo-revivalism Islam. Those views of the KAMMI, however are weak in two aspects. First, the historical aspect where the normative idea and the contextual reality sometimes do not meet each other. This happen by the second, the lack of methodology in which the KAMMI sometimes bring them to the narrow-minded and trap them in dilemma.